Effects of COVID-19 Lockdown on Tumour Burden of Melanoma and Cutaneous Squamous Cell Carcinoma - Antonio Tejera-Vaquerizo; Sabela Paradela; Agusti Toll; Jorge Santos-Juanes; Ane Jaka; Alba López; Javier Cañueto; Àlvaro Bernal; Isabel Villegas-Romero; Carla Fernández-Pulido; Héctor Perandones; David Moreno-Ramírez; et al. (Medical Journals Sweden, 2021)
The aim of this study was to compare tumour burden in patients who underwent surgery for melanoma and cutaneous squamous cell carcinoma during nationwide lockdown in Spain due to COVID-19 (for the period 14 March to 13 June 2020) and during the same dates in 2019 before the COVID-19 pandemic. In addition, associations between median tumour burden (Breslow thickness for melanoma and maximum clinical diameter for cutaneous squamous cell carcinoma) and demographic, clinical, and medical factors were analysed, building a multivariate linear regression model. During the 3 months of lockdown, there was a significant decrease in skin tumours operated on (41% decrease for melanoma (n = 352 vs n = 207) and 44% decrease for cutaneous squamous cell carcinoma (n = 770 vs n = 429)) compared with the previous year. The proportion of large skin tumours operated on increased. Fear of SARS-CoV-2 infection, with respect to family member/close contact, and detection of the lesion by the patient or doctor, were related to thicker melanomas; and fear of being diagnosed with cancer, and detection of the lesion by the patient or relatives, were related to larger size cutaneous squamous cell carcinoma. In conclusion, lockdown due to COVID-19 has resulted in a reduction in treatment of skin cancer.